The Indonesia update - Australian National University. Indonesia Project; Institute of Southeast Asian Studies (Singapore : Institute of Southeast Asian Studies, 2005)
The annual Indonesia update, organized by the Indonesia Project at the Australian National University, Canberra, has been a forum for expert commentators, leading researchers, and policymakers for nearly two decades. The series of books produced from this lively forum continues to be a key reference on trends in Indonesian socio-economics and political culture. Since 1994, the Update series has been published by ISEAS in Singapore. This CD contains the full-text versions of all the books produced in the Update series from 1988 to 2004. You can read, search by author, topic, keyword and print out from the CD-ROM
aIndonesia assessment 1988 -- Indonesia assessment 1990 -- Indonesia assessment 1991-- Indonesia assessment 1992, political perspectives on the 1990s -- Indonesia assessment 1993, labour, sharing in the benefits of growth? -- Indonesia assessment 1994, finance as a key sector in Indonesia's development -- Indonesia assessment 1995, development in eastern Indonesia -- Indonesia assessment, population and human resources -- Indonesia's technological challenge -- Post-Soeharto Indonesia, renewal or chaos? -- Indonesia in transition, social aspects of reformasi and crisis -- Indonesia today, challenges of history -- Women in Indonesia, gender, equity, and development -- Local power and politics in Indonesia, decentralisation & democratisation -- Business in Indonesia, new challenges, old problems
Title from disc label
System requirements for PC: 256 MB RAM (512 MB recommended); Windows 95, Windows 98, Windows 2000 or Windows XP; PDF viewer application; 640 x 480 display (800 x 600 recommended)
System requirements for Macintosh: 256 MB RAM (512 MB recommended); Mac OS 8.6 or above; PDF viewer application; 640 x 480 display (800 x 600 recommended)
Keywords: Indonesia -- Economic conditions -- 1966-1997; Indonesia -- Economic conditions -- 1997-; Indonesia -- Economic policy; Indonesia -- Politics and government -- 1966-1998; Indonesia -- Politics and government -- 1998-